Integral field spectroscopy of luminous infrared main-sequence galaxies at cosmic noon. Issue 4 (26th February 2021) - Hogan, L; Rigopoulou, D; Magdis, G E; Pereira-Santaella, M; García-Bernete, I; Thatte, N; Grisdale, K; Huang, J-S
ABSTRACT: We present the results of an integral field spectroscopy survey of a sample of dusty (ultra) luminous infrared galaxies (U/LIRGs) at 2 < z < 2.5 using KMOS on the Very Large Telescope. The sample has been drawn from Herschel deep field surveys and benefits from ancillary multiwavelength data. Our goal is to investigate the physical characteristics, kinematics, and the drivers of star formation in the galaxies whose contribution dominates the peak of the cosmic star formation density. Two-thirds of the sample are main-sequence galaxies in contrast to the starburst nature of local U/LIRGs. Our kinematic study, unique in its focus on z ∼ 2 dusty star-forming galaxies, uses the H α emission line to find that ∼40 per cent appear to be isolated discs based on the ratio of rotational velocity to the velocity dispersion, suggesting steady-state mechanisms are sufficient to power the large star formation rates (SFRs). The ratio of obscured to unobscured star formation indicates the sample of galaxies experiences less dust obscuration compared to intermediate and local counterparts, while also hosting cooler dust than local U/LIRGs. In addition to H α we detect [N ii ] 6583 Å in our targets and show the gas-phase metallicities do not exhibit the metal deficiency of local U/LIRGs. These results indicate that, despite their extreme IR luminosity, the underlying mechanisms driving the massive SFRs found at cosmic noon are due to scaled up disc galaxies as opposed to mergers.